What do we know about the future of food systems in Central and West Asia and North Africa? - Frija, Aymen (International Food Policy Research Institute, 2025)
The subregions of Central and West Asia and North Africa (CWANA) will continue to import around 50 percent of domestic food requirements by 2050.